Characterisation of ancient Roman wall‐painting fragments using non‐destructive IBA and MA‐XRF techniques. (12th July 2020) - Vadrucci, Monia; Mazzinghi, Anna; Sorrentino, Beatrice; Falzone, Stella; Gioia, Claudia; Gioia, Patrizia; Loreti, Ersilia M.; Chiari, Massimo
Abstract : Scientific investigation is very important in studies addressing issues of archaeological and historical objects. Ion beam analysis (IBA) and macro X‐ray fluorescence (MA‐XRF) spectroscopy are remarkable tools to obtain information about elemental composition and imaging of historical artefacts with a non‐invasive character. These investigation techniques were employed in the framework of a project aimed at supporting the characterization of materials and techniques related with the Roman wall painting. The archaeological excavations at Villa della Piscina in Rome have revealed a luxury building with a large pool (about 50 m long) and thermal baths and numerous fragments of plaster, coming from intentional demolitions referable to two distinct architectural contexts of the Villa during the imperial age, have been found. This work deals with studying the interesting wall pictorial apparatus of great cultural value of the heritage inherited from the Roman age in the area of the ancient city of Rome. The colour palette of the pigments investigated, in particular, by MA‐XRF and particle‐induced X‐ray emission (PIXE) and has revealed Fe, Cu, Pb, Si and Hg as main elements. Traces of other constituents uncover the choice of the different colours chosen by the artists who had embellished the rooms of the Villa.